THE EFFECT OF WORK-LIFE BALANCE AND CAREER DEVELOPMENT ON WORK ENGAGEMENT WITH MEDIATED JOB SATISFACTION OF GEN Y AND Z NON ACADEMIC STAFF AT UNIVERSITY “A” - Priambada, Antanius Daru; Wulani, Fenika (Research In Management and Accounting (RIMA), 2025)
Organizations need highly engaged workers if they want to achieve great performance. This study investigates work-life balance, career development, and job satisfaction as antecedents of work engagement. This study uses a survey design with questionnaires distributed to Generation Y and Z non academic staff working at a university in Java. Partial Least Squares - Structural Equation Modelling (PLS-SEM) with SmartPLS 4.0 software was used to analyse the 80 responses gathered. Our study finds that work life balance can increase work engagement directly and also through job satisfaction. However, career development can only increase work engagement if employees are satisfied first with their job. This result highlights the importance of universities in designing jobs to ensure employees perceive work-life balance since they have time to enjoy their personal activities. In addition, universities need to create career opportunities for employees that increase their job satisfaction and boost their level of work engagement.